The Effect of Educational Video Media Use on Knowledge of Balanced Eating Patterns in School-Age Children at SDN Serua 3 Depok - Muhammad Abhista Hakim; Avliya Quratul Marjan (Civiliza Publishing, 2026)
Nutritional issues among school-aged children remain a challenge in Indonesia, including in the Bojongsari Community Health Center work area. Children are at risk of malnutrition or overnutrition due to diets that do not follow balanced nutrition guidelines, such as consuming fast food high in sugar, salt, and fat. This condition can affect children's health, growth, and academic performance. Therefore, effective educational interventions are needed to improve children's understanding of healthy eating habits. This activity aimed to determine the effect of animated educational video media on balanced nutrition knowledge in school-aged children. The intervention was conducted offline at SDN Serua 3, Depok City, involving 30 fifth-grade students. The animated video